Reengineering framework for open source software using decision tree approach - Jaswinder Singh; Kanwalvir Singh; Jaiteg Singh (Institute of Advanced Engineering and Science, 2019)
A Software engineering is an approach to software development. Once software gets developed and delivered, it needs maintenance. Changes in software incur due to new requirements of the end-user, identification of bug in software or failure to achieve system objective. It has been observed that successive maintenance in the developed software reduces software quality and degrades the performance of software system. Reengineering is an approach of retaining the software quality and improving maintainability of the software system. But the question arises “when to reengineer the software”. The paper proposed a framework for software reengineering process using decision tree approach which helps decision makers to decide whether to maintain or reengineer the software systems.